Analytical study to assess fetal and perinatal outcome in booked and unbooked obstetric cases - Chourasia, Sapna; Yadav, Kamlesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: The high perinatal mortality rates are indicators of the poor state of health services and it is pertinent to determine the relationship between the booking status of mother and fetal outcomes. Methods: In the present randomized prospective study of 400 unbooked (study group) obstetric cases were evaluated and compared with 400 booked (control group) obstetric cases over a period of one year. Results: Perinatal outcomes of women in study group were significantly poorer than women in control group due to high preterm delivery, LBW, with low Apgar score at five minutes, with more NICU admission due to RDS, with high perinatal mortality in term of IUD, early neonatal deaths in study group. Conclusions: Findings of the study will help the programmers and service providers in identifying areas where emphasis has to be given in the development of strategies that will promote the utilization of antenatal services, to reduce adverse perinatal and fetal outcome.